Developing people and the corporate culture in financial services - Stanić, Vlad.; Boyle, Denis (Boca Raton, Fla : CRC Press, 1999)
Aims to provide guidelines for the management of change across this rapidly-developing and fast-converging industry. The emphasis throughout is on the practical implementation of change management strategies, as employed by those who are at the cutting edge of the international financial services community today.
Includes index.
gau 02/08/2016
Loans
Keywords: Financial services industry - Management; Financial services industry; Corporate culture; Managing people